TREATMENT OF TEXTILE DYE EFFLUENT BY ALGAE: AN ECO-FRIENDLY AND SUSTAINABLE APPROACH TO THE ENVIRONMENTAL POLLUTION - SUBHASHA NIGAM,; SURBHI SINHA,; SUBHASHA NIGAM,; MAYUR MANGLIK,; RACHANA SINGH, (International Journal of Pharma and Bio Sciences, 2016)
An increasing number of toxic dyes in aquatic ecosystem have become a matter of concern worldwide over the last few decades; hence, they need to be remedied. These pollutants enter the aquatic ecosystem as a result of various industrial activities. A number of physical, chemical and biological methods have been developed for the treatment of waste waters and among these, the use of algae is considered as a more eco-friendly and economical approaches. Algae are organisms which execute multiple roles in the environment like bioremediation of wastewater, drawing of excess nutrients and in turn, produce biomass, which has a large number of uses in the food, biofuel and pharmaceutical industries. This article deals with the removal of hazardous dyes by living, dead / immobilized forms of algae. These algae are capable of uptake of different types of dyes such as azo, reactive, basic etc under various optimum conditions like pH, temperature, concentration of dyes and biomass, etc.